Internalization Of Islamic Education In The Independent Curriculum From Ibnu Taimiyah's Perspective - Alivia Tri Handayani; Triono Ali Mustofa (At-Tarbiyat, 2023)
The Merdeka Curriculum as the newest curriculum in Indonesia which is used as a reference for education is a new hope in the world of education. Islamic education is no exception. Islamic education as a way of broadcasting Islam has a foundation on ideas which are ideologically sourced directly from the Qur'an and Hadith. However, the development of traditions that occur in society makes Islamic education also influenced by community traditions. Ibnu Taimiyah as one of the Islamic intellectual figures who grew up among the Hambali school of thought made him one of the Islamic intellectual figures who persistently reformed traditions that contradict the Al-Qur'an and Hadith. The method used by the author in conducting his research is the library research method or also known as library research. Which sources in this study come from books or literature that are related to the concept of Islamic education, the independent curriculum, and the concept of Islamic education itself according to the perspective of the figure of Ibnu Taimiyah. The concept of independent learning as a form of the new education curriculum is in line with the concept of education put forward by Ibn Taimiyah. In this case, Ibn Taimiyah emphasizes two main methods, namely scientific and iradiyah. Which of the two methods are also implemented in the independent curriculum through freedom in learning and students who are used as the core in carrying out the learning process.